2019
DOI: 10.3390/app9245410
|View full text |Cite
|
Sign up to set email alerts
|

A Stress Analysis of a Conical Pick by Establishing a 3D ES-FEM Model and Using Experimental Measured Forces

Abstract: This paper presents a procedure for an accurate and reliable stress analysis in a conical pick used in mining operations, aiming to improve their wear resistance. This is achieved by (1) establishment of a three-dimensional (3D) edge-based smoothed finite element method (ES-FEM), and algorithms of creating the smoothing domain for accurate solution in terms of stress and strain distributions; and (2) use of experimentally measured actual forces using a full-scale rotary cutting machine. In our 3D ES-FEM model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…The energy consumption for the strip cutting was 3.7695 × 10 5 J. In the process of cutting rock with a sawblade, when the sawblade cuts into the rock vertically, the volume of rock cut was 178 823 mm 3 . In process of cutting rock at a constant depth, the rock volume cut was 281 043.7 mm 3 , and the rock volume removed by a single slit sawblade was 459 866.7 mm 3 .…”
Section: Comparison Of Specific Cutting Energymentioning
confidence: 99%
See 1 more Smart Citation
“…The energy consumption for the strip cutting was 3.7695 × 10 5 J. In the process of cutting rock with a sawblade, when the sawblade cuts into the rock vertically, the volume of rock cut was 178 823 mm 3 . In process of cutting rock at a constant depth, the rock volume cut was 281 043.7 mm 3 , and the rock volume removed by a single slit sawblade was 459 866.7 mm 3 .…”
Section: Comparison Of Specific Cutting Energymentioning
confidence: 99%
“…The numerical simulation results showed that the influences of the number of tapered picks, installation angle, and cutting position on the cutting performance of the cylinder gradually decreased. Fan et al [3] simulated the rockcrushing process of a conical pick using a three-dimensional (3D) finite-element model based on smooth edges. Zhou et al [4,5] studied the influence of the cone angle, cutting angle, and cutting speed of a cone pick on rock crushing dust and indicated that increasing the cone and cutting angles of the cone pick is conducive to reducing dust generation.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the serious wear types of conical pick with mining equipment, it was found that the wear decreases and increases with the increase of pick cutting angle and inclination angle, respectively [10]. ES-FEM (edge-based smoothed nite element method) and PFC numerical models of conical pick were built by Fan et al [11] and Zhang et al [12], respectively, which o ered the solutions to improve the wear resistance of pick.…”
Section: Introductionmentioning
confidence: 99%
“…Yasar and Yilmaz 7 conducted cutting experiments on six different rock samples by using rock vertical cutting machine to research the changes of cutting force and specific cutting energy consumption with the increase of cutting depth and ratio of cutting line spacing to cutting depth, in 2019. And in 2019, Fan et al 8 used the three-dimensional finite element model based on the smooth edge to simulate the rock breaking process with the conical pick. In 2019, Wang and Su 9 conducted the indentation test of rock broken by conical pick based on rock fracture mechanics, and investigated the influencing factors of rock broken with conical pick combined with Evan's rock breaking theory.…”
Section: Introductionmentioning
confidence: 99%